An integrated subtractive genomics and immunoinformatic approach for designing a multi-epitope peptide vaccine against methicillin-resistant Staphylococcus aureus - Subramani, Nandha Kumar; Venugopal, Subhashree; Rajan, Anand Prem (Frontiers in Bioinformatics, 2026)
IntroductionMRSA is a multi-drug-resistant bacteria responsible for severe infections that has become a major health concern. Due to constraints of traditional methods, there is a need for developing a new approach to prevent the MRSA-related infections by targeting key pathogens.MethodsInitially, the subtractive genomics was applied to the MRSA proteome to identify non-homologous, essential, and virulence targets using comparative BLAST-based screening. Further, immunoinformatic tools were employed for B- and T-cell epitope prediction and vaccine construction with appropriate adjuvants and linkers, followed by immune simulation and molecular docking with immune receptors.ResultsComparative metabolic pathway analysis identified 294 MRSA pathway proteins, with acetolactate synthase (ALS) as a non-homologous, essential, and virulent protein that is involved in the branched amino acid biosynthesis pathway. The constructed ALS vaccine consists of 3 B-cell and 19 T-cell epitopes exhibited stable immunological features with 97.55% global population coverage. Molecular docking revealed that ALS exhibited a superior binding affinity with the TLR4 receptor (−1,438.7 kcal/mol) than the TLR2 receptor (−1,103.5 kcal/mol), which was further confirmed by high structural stability and compactness analysis. Immune simulations also exhibited elevated IgM, IgG subtypes, and cytokine productions, suggesting a robust humoral and cellular immunity.DiscussionIdentified ALS highlights its biological relevance in MRSA survival. The stability predictions with TLR4 suggested effective activation of innate immunity that may enhance antigen presentation and downstream adaptive immunity. The validation of the ALS vaccine’s safety and immunogenicity further requires comprehensive in vitro and in vivo examinations.ConclusionThus, ALS is recognized as a promising MRSA vaccine candidate and has the potential to activate immune responses effectively.